Comprehensive program development for congenital heart disease in the United Arab Emirates and in Singapore - Kiraly, Laszlo; Aye, Maung Maung Winn; Subbian, Senthil Kumar; Shah, Nishant Chandrakant; Hetharsi, Balazs; Al Hakami, Aref Mohammed; Kofidis, Theo (Journal of Humanitarian Cardiovascular Medicine, 2023)
Background/Objective. Establishment and development of tertiary-care centres for congenital heart disease (CHD) face multiple challenges as they need to be accessible, affordable/sustainable and provide the best possible outcomes. We report our experience of foundation a new tertiary-care CHD centre in the United Arab Emirates (UAE) and program development in Singapore. Methods. Prevalence and incidence of CHD in the context of local sociocultural environment was reviewed. Having established program elements of team, premises and workflow, quality assurance system was established. Outcome analysis, continuous audit modified internal therapeutic policies in accordance to international databases. Results. Consanguinity, segregated pattern of the population, high birth rate and low prenatal screening rate increased the incidence/prevalence and complexity of CHD in the UAE. Higher complexity/redo presentation and presence of associated anomalies were prevalent in Singapore at a lower birth rate. Increasing patient-load, strict professional working environment, strong governmental financial mandate for care nominated our centre into a market-leading position in the UAE. Singapore has a highly-developed, regulated, still competitive healthcare infrastructure that represents challenges for program development. Additional surgical activity from underserviced regions could provide the adequate CHD patient-pool that is critical to achieve team-expertise and ensure the best possible patient and program outcomes. Conclusion. CHD has significant public health aspects, however, new and/or developing centres face different challenges depending on the sociocultural and economic environment they function in. External demographic factors, case-load, complexity, referral patterns, health-care financing structure are difficult to adjust; internal factors: program structure, quality assurance, professional working framework are subjects for improvement.